Custody Evaluators' Beliefs about Domestic Abuse Allegations, 2009-2010 (United States) - Saunders, Daniel ([Verlag nicht ermittelbar], 2015)
This study sought to further understanding of the beliefs of child custody evaluators and related professionals regarding allegations of domestic abuse made by parents during the divorce process. Researchers administered a survey of beliefs, practices, background, and training experiences to custody evaluators. For comparison purposes, judges, legal aid attorneys, private attorneys, and domestic violence program workers were also surveyed. Additionally, researchers used in-depth qualitative interviews of domestic abuse survivors to help interpret quantitative findings, to understand the complexities of their experiences, and to generate hypotheses for future research. The study had two major parts. Part 1 (Custody Evaluator Beliefs Dataset) was a survey of professionals, who had experience with custody cases (child custody evaluators, judges, attorneys, and domestic violence program workers). The dataset includes 1,246 cases and 162 variables. Part 2 (Qualitative Transcripts of Survivors' Interviews) involved qualitative, semi-structured interviews with domestic abuse survivors who experienced negative outcomes in family court. Part 2 contains interviews with 24 with domestic abuse survivors.